The spatial spillover and nonlinear effects of green technology innovation on regional energy intensity in China - Zeng, S; Su, B; Fu, X; Li, G; Zhong, Z (Taylor and Francis, 2021)
Green technology innovation (GTI) helps to promote the transformation of energy development and achieve low-carbon development. This paper evaluates the effect of GTI on energy intensity (EI) using a sample of China's provincial panel data from 2001 to 2019. First, using a mediation effect model, we study the potential pathways of GTI that affect EI. Moreover, we examine whether the GTI has a spatial spillover and threshold effect by using the spatial econometric model and threshold regression. The results show that there is a positive effect of GTI on reducing EI, and this effect is partly realized through the industrial structure transformation and upgrading. In addition, the influence has a spatial spillover effect between regions. Finally, we find that GTI has heterogeneous effects on EI due to differences in regional economic development levels.